Inhibition of carbon tetrachloride-mediated apoptosis and oxidative stress by melatonin in experimental liver fibrosis - Ogeturk, M.; Kus, I.; Pekmez, H.; Yekeler, H.; Sahin, S.; Sarsilmaz, M. (Sage Publications Inc, 2008)
Melatonin, the principal secretory product of the pineal gland, functions as a potent antioxidant and free radical scavenger. Additionally, the antiapoptotic effect of melatonin has been observed both in vivo and in vitro. The aim of this experimental study was to investigate the protective effects of melatonin against carbon tetrachloride (CCl4)-induced apoptosis and oxidative stress in rat liver. Twenty-four male Wistar rats were divided in three equal groups. Group I was used as control. Rats in group II were injected every other day with CCl4 (0.5 mL/kg BW) for a month, whereas rats in group III were treated every other day with the same dose Of CCl4 plus melatonin (25 mg/kg BW). At the end of the experiment, all animals were killed by decapitation and the livers were rapidly removed. Some of the liver tissue specimens were used for determination of malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) levels. The remaining tissue specimens were processed for immunohistochemical assessment, and the percentage rates of apoptotic liver cells stained with immunoreactive Bax were determined. Chronic administration of CCl4 significantly increased liver MDA contents, as an end product of lipid peroxidation, and also significantly decreased SOD and GSH-Px activities, emphasizing the generation of increased oxidative stress. Moreover, it caused an evident increase in apoptotic cells. Melatonin treatment significantly reduced MDA levels and elevated SOD and GSH-Px activities in rats received CCl4 Plus melatonin. Furthermore, apoptotic changes caused by CCl4 were considerably decreased in these animals. The results of the present study indicate that melatonin treatment substantially prevents CCl4-induced apoptosis and oxidative damage in the liver. Thus, melatonin may serve as a drug for treating many clinical conditions that arise from inappropriate apoptosis. Toxicology and Industrial Health 2008; 24: 201-208.
Keywords: apoptosis; carbon tetrachloride; liver; melatonin; oxidative stress